A sum-based discrete event-triggered dynamic output feedback control for interval type-2 fuzzy systems. (October 2022) - Zhang, Duo; Zhang, Liruo; Yu, Zhongjing; Shu, Lan; Swain, Akshya Kumar
Abstract: The current study concentrates on the event-based controller design for nonlinear networked systems characterized by the interval type-2 (IT2) fuzzy model. An innovative sum-based discrete event-triggered mechanism (SDETM), whose triggering condition includes several previous measurement samples, is proposed. Compared to the traditional event-triggered mechanism (ETM), the novel SDETM requires less network resources consumption. A dynamic output feedback controller (DOFC) is designed to achieve stability of the system. A novel stability criteria is established via the Lyapunov–Krasovskii functional method with the prescribed H ∞ performance. Co-design of the DOFC and SDETM parameters is carried out using the cone complimentarity linearization (CCL) algorithm. The effectiveness of the proposed method is demonstrated with two practical cases. Highlights: A sum-based discrete event-triggered mechanism (SDETM) is proposed, with which the communication resources can be significantly saved. Closed-loop stability of the interval type-2 fuzzy system is achieved using a dynamic output feedback controller. A novel stability criteria is established via the Lyapunov–Krasovskii functional method with prescribed H ∞ performance. Using the Cone Complimentarity Linearization (CCL) algorithm, the co-design of controller parameters and SDETM parameters is accomplished. The effectiveness of the proposed method is demonstrated with two practical cases.